INTEGRATION OF RELIGIOUS MODERATION IN TAFSIR LEARNING AND STRENGTHENING MODERATE ATTITUDES OF STUDENTS IN THE QUR’ANIC STUDIES AND TAFSIR PROGRAM IN BENGKULU - Nurma Yunita; Hasep Saputra; Alven Putra (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2025)
This study examines how moderate hermeneutics is integrated and enacted within Qur’anic exegesis (tafsir) courses and how these pedagogical choices relate to students’ dispositions toward religious moderation in an Indonesian Islamic higher-education setting. Using a qualitative descriptive design, we analyzed course documents (11 syllabi/RPS), conducted classroom observations (n=12 sessions), and interviewed lecturers (n=6) and students (n=24) purposively sampled across cohorts. Data were thematically coded with analyst triangulation and member checking. Three integration pathways were identified: (1) canon selection privileging Indonesian and maqāṣid-oriented tafsir (e.g., al-Misbah, al-Azhar), (2) dialogic routines that normalize interpretive plurality and disagreement, and (3) assessment shifts from recall to reflective and context-applied tasks. Students reported increased comfort with difference and heightened sensitivity to justice- and mercy-oriented Qur’anic values; however, attitudinal change varied with prior schooling and organizational affiliations. The study contributes an actionable model linking hermeneutical stance to pedagogical routines and affective outcomes in interpretive education. Findings suggest that explicitly framing wasat}iyyah within textual analysis, coupled with dialogic pedagogy, is associated with stronger moderation dispositions, underscoring the need for systematic outcome measures and longitudinal follow-up.